Enhanced dark hydrogen fermentation by addition of ferric oxide nanoparticles using Enterobacter aerogenes. (May 2016) - Lin, Richen; Cheng, Jun; Ding, Lingkan; Song, Wenlu; Liu, Min; Zhou, Junhu; Cen, Kefa
Graphical abstract: Highlights: Effect of γ-Fe2 O3 nanoparticles on H2 fermentation using E . aerogenes was studied. Addition of 200 mg/L nanoparticles enhanced H2 production by 17.0% from glucose. Hydrogenase activity and electron transfer were enhanced by 200 mg/L nanoparticles. SEM and TEM were used to investigate bacteria changes in response to nanoparticles. Abstract: Ferric oxide nanoparticles (FONPs) were used to facilitate dark hydrogen fermentation using Enterobacter aerogenes . The hydrogen yield of glucose increased from 164.5 ± 2.29 to 192.4 ± 1.14 mL/g when FONPs concentration increased from 0 to 200 mg/L. SEM images of E. aerogenes demonstrated the existence of bacterial nanowire among cells, suggesting FONPs served as electron conduits to enhance electron transfer. TEM showed cellular internalization of FONPs, indicating hydrogenase synthesis and activity was potentially promoted due to the released iron element. When further increasing FONPs concentration to 400 mg/L, the hydrogen yield of glucose decreased to 147.2 ± 2.54 mL/g. Soluble metabolic products revealed FONPs enhanced acetate pathway of hydrogen production, but weakened ethanol pathway. This shift of metabolic pathways allowed more nicotinamide adenine dinucleotide for reducing proton to hydrogen.